Anti-Dengue ED3 Long-Term Immune Response With T-Cell Memory Generated Using Solubility Controlling Peptide Tags - Islam, Mohammad M.; Miura, Shiho; Hasan, Mohammad N.; Rahman, Nafsoon; Kuroda, Yutaka (Frontiers in Immunology, 2020)
Recombinant proteins are an attractive choice as a safe alternative to traditional live attenuated vaccines. However, most small size proteins are poorly immunogenic, and adjuvants, whose mode of action remains to be fully clarified, are needed for increasing their immunogenicity. Here, we report the effects of short solubility controlling peptide tags (SCP-tags) on the immunogenicity of DENV3 envelope protein domain 3 (3ED3; 103 residues, 11.46 kDa) in ICR and Swiss albino model mice. The attachment of a 4-Ile SCP-tag (C4I-tag) increased the hydrodynamic radius of 3ED3 from 2.2±0.09 to 111±146 nm as assessed by Dynamic Light Scattering in PBS at 37°C, indicating that the C4I-tag oligomerized 3ED3. Immunization at 30µg/dose showed that the untagged 3ED3 was not or poorly immunogenic, whereas the C4I-tag increased its immunogenicity by up to 39 fold as assessed by IgG level using ELISA. Moreover, the increased antibody level was sustained for over six months after immunization and a high number of effector and central memory T-cells were generated. These observations provide direct and quantitative evidence for the hypothesis that subvisible aggregates with hydrodynamic radii of 100 nm can increase immunogenicity and that SCP-tag can establish a long-term, target-specific immune response in a way adequate for the development of a peptide/protein-based DENV vaccine.